Identification of complex network topologies through delayed mutual information. Issue 2 (2020) - Toupance, Pierre-Alain; Chopard, Bastien; Lefevre, Laurent
Abstract: The definitions of delayed mutual information and multi-information are recalled. It is shown how the delayed mutual information may be used to reconstruct the interaction topology resulting from some unknown scale-free graph with its associated local dynamics. Delayed mutual information is also used to solve the community detection problem. A probabilistic voter model defined on a scale-free graph is used throughout the paper as an illustrative example.